2021
DOI: 10.1038/s41598-021-99370-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters and biological markers associated with acute severe ocular complications in Stevens-Johnson syndrome and toxic epidermal necrolysis

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe cutaneous adverse drug reactions with high mortality rates. Its sequelae, such as blindness, persist even after recovery. Patients with SJS/TEN should be accurately diagnosed and receive appropriate treatment as soon as possible. Therefore, identifying the factors for severity prediction is necessary. We aimed to clarify the clinical parameters and biological markers that can predict acute severe ocular complications (SOCs) in SJS/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…From our ThaiSCAR recent study, body surface area detachment of ≥10% was a significant predictive factor for acute SOCs. In addition, serum levels of inflammatory mediators, especially S100A8/A9 and granulysin, showed a significantly higher trend in the severe group compared to those of non-severe individuals ( Panpruk et al, 2021 ).…”
Section: Severe Cutaneous Adverse Drug Reactions In Thai Population: ...mentioning
confidence: 90%
“…From our ThaiSCAR recent study, body surface area detachment of ≥10% was a significant predictive factor for acute SOCs. In addition, serum levels of inflammatory mediators, especially S100A8/A9 and granulysin, showed a significantly higher trend in the severe group compared to those of non-severe individuals ( Panpruk et al, 2021 ).…”
Section: Severe Cutaneous Adverse Drug Reactions In Thai Population: ...mentioning
confidence: 90%
“…There have been much fewer studies focusing on biomarkers to monitor severity, progression, and response to therapy during the acute stages of SJS/TEN and how these correlate with long-term morbidity and delayed mortality. Biomarkers that have been studied either singly or in combination in SJS/TEN include procalcitonin ( 32 ); granulysin ( 123 ); IFN-g ( 124 ); interleukin (IL)-8 and granzyme B ( 125 ); endocan, tumor necrosis factor-α, vascular endothelial growth factor, and C-reactive protein; serum IL-17 ( 126 ); complement components ( 127 ); alarmins like the heterodimeric form of S100 calcium-binding protein A8 and S100 calcium-binding protein (A9 S100A8/A9) ( 123 ); chemokines like CXCL9/MIG and CXCL10/IP-10 ( 124 ); antimicrobial peptides like LL-37 ( 128 ); exosomal nucleic acids like miR-375-3p ( 129 ); plasma lipid profiles ( 130 ); renal functions ( 78 , 79 ); neutrophil:lymphocyte ratio; and C-reactive protein:albumin ratio ( 131 ).…”
Section: Potential Future Research Directionsmentioning
confidence: 99%
“…In a previous study, we identified that S100A8/A9 and granulysin levels may help predict the occurrence of severe ocular complications in SJS/TEN 11 . However, the role of cytokines and chemokines in association with histopathologic features and the progression of the skin disease is not fully understood.…”
Section: Introductionmentioning
confidence: 99%